Anomali Perlakuan Akuntansi atas Nilai Aset Budaya: Studi Kasus Goa Janji Kabupaten Bone - Nurfadilah Rahmadani; Zaskia Asmiranda; Widia Natasya; Andi Devtriana Alya Nabila; Salwa Salwa; Muhammad Yamin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Heritage assets possess unique characteristics because they embody historical, cultural, and social values that cannot be fully represented through monetary-based accounting approaches. This study aims to analyze the anomaly in the accounting treatment of heritage asset values through a case study of Goa Janji in Bone Regency. The research employed a qualitative approach using a case study method. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that Goa Janji meets the characteristics of a heritage asset and qualifies for recognition as a government asset under the Government Accounting Standards because it is controlled by the local government and provides service potential to the public. However, an anomaly was identified in the measurement aspect due to the absence of historical cost, the lack of an active market, and the dominance of historical, cultural, and social identity values that cannot be measured reliably. The study concludes that the disclosure of heritage assets should be complemented by narrative information in the Notes to the Financial Statements to provide a more comprehensive representation of their cultural value.